Learning Curves in Laparoscopic Training: Comparative Analysis of Two Training Models - Settaf-Cherif, Layla; Ostrowski, Adam; Khan, Anmol; Malinowska, Katarzyna; Kwiatkowska, Oliwia; Paszylk, Łukasz; Lipowski, Paweł; Adamowicz, Jan; Drewa, Tomasz (Journal of Education, Health and Sport, 2025)
Introduction: Laparoscopic surgery is widely used due to its minimal invasiveness, shorter recovery times, and improved patient outcomes. However, it demands advanced psychomotor skills, such as spatial awareness, precision movements, and hand-eye coordination. Mastering these skills requires structured and effective training strategies. Developing and maintaining laparoscopic proficiency is essential for medical students preparing for clinical practice. Purpose: This study aimed to compare the efficacy of intensive and distributed laparoscopic training models in developing and retaining laparoscopic surgical skills among medical students. Materials and Methods: A prospective study was conducted from July to December 2024, involving 10 medical students (6 females, 4 males, aged 20-26 years) with no prior laparoscopic experience. Participants were divided into two training groups: intensive (daily sessions over 10 days) or distributed (twice weekly sessions over 5 weeks). Training included standardized exercises (peg transfer, circle cutting, needle guidance, ball allocation) using the Laparo Advance box trainer with E-BLUS-modified protocols. Performance was evaluated based on task completion times and errors, with follow-up assessments one month post-training. Results: Both training models improved laparoscopic skills, but the distributed group showed superior skill retention and consistency. One month follow-up evaluations showed significantly shorter task times completion in the distributed group for peg transfer (p=0.014, d=1.97) and cutting a circle (p=0.036, d=1.74). Conclusions: Distributed training demonstrated superiority in skill retention, error reduction, and consistent task performance, especially in tasks requiring precision. These findings support integrating distributed training into laparoscopic education to improve skill acquisition and better prepare trainees for clinical practice.